Individualized Education Plans: What Characterizes the Research? - Bachke, Carl Crh. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This study illuminates the research question what characterizes the research of Special Needs Education’s (SNE’s) use of Individualized Education Plans (IEP), during the period 2010-2015? A sample of 11 relevant Norwegian publications has been analyzed by means of these criteria: Type of publication, research method(s) applied, sub-topics focused on and perspectives of SNE. Findings show (1) the amount of the research is still scarce, (2) only three researchers of PhD-level or above have participated in this sample of publications, (3) the sample demonstrates various research methods applied, although document analysis dominates, (4) there is still a need of research looking for catalysts of good planning and using of IEP, (5) the study presents one way of constructing thematic and sub-topical categories, and (6) one needs to validate how the SNE’s perspectives of traditionalism and inclusionism influence the outcomes of IEP research.